Digital Learning Strategies for Elementary Education: Exploring Effective Techniques - Selirowangi, Nisaul Barokati; Wajdi, Muh Barid Nizarudin (STAI Miftahul Ula Nganjuk, 2022)
The aim of this research is to delve into the multifaceted domain of digital learning strategies in elementary education. It encompasses an introduction that recognizes the transformative shift in education fueled by digital technologies and acknowledges persisting challenges. The research methodology employs a library research approach, systematically searching academic databases and reputable sources, applying inclusion criteria, and extracting data for analysis. The results elucidate a nuanced understanding of digital learning's potential, emphasizing the necessity for holistic approaches, intentional design in gamification, communal learning spaces, and an unwavering commitment to equity. This study aims to propel transformative actions in elementary education, advocating for comprehensive integration, intentional design, collaborative learning, and a steadfast focus on equity within the evolving landscape of digital education.